Pemanfaatan Teknologi dalam Mewujudkan Sustainable And Productive Life Masyarakat Kelurahan Pradah Kalikendal, Kecamatan Dukuh Pakis, Surabaya - Prihartini Widiyanti; Franky Chandra Satria Arisgraha; Fitriyatul Qulub (I-Com: Indonesian Community Journal, 2024)
One of the problems that exist in the community of Pradah Kalikendal Village, which is the largest sub-district in Dukuh Pakis District, Surabaya, is the waste of water that occurs during ablution and increasing chronic fatigue in the community which has an impact on reducing community productivity. Based on this, Airlangga University launched a community service program with the theme "Utilization of Technology in Realizing Sustainable and Productive Life in Pradah Kalikendal Village, Surabaya" which aims to increase water conservation and prevent fatigue and maintain community productivity through the application of technology, such as the use of automatic water taps. with a filter that can turn off when there is no object that stimulates the sensor and a fatigue detection tool to determine the individual's fatigue condition. This is necessary to prevent health problems and maintain the individual's fitness status. The program objectives are (1) water conservation: Using automatic sensor faucet technology to reducing water waste, especially in public service areas such as sub-districts, health centers and places of worship and (2) maintaining productivity: using a microcontroller-based fatigue detection tool to monitor the fatigue of people involved in intensive physical activity. This program involves Airlangga University students as part of the implementation of the Independent Learning Campus (MBKM) policy, which provides direct experience for students to interact with the community and solve real problems. This program takes the form of training on the use of technology-based tools in the form of filtered water taps for local residents, especially At-Taqwa mosque administrators and Dukuh Kupang Health Center medical personnel, for water conservation and the use of work fatigue detectors. Evaluation is carried out through questionnaires and community testimonials to measure the effectiveness of the program.